Biological Response Following Inlay Arthroplasty of the Knee: Cartilage Flow Over the Implant. (April 2018) - Beyzadeoglu, Tahsin; Pehlivanoglu, Tuna
Objective: Inlay arthroplasty (IA) has seen growing interest as a new primary arthroplasty intervention for patients that need to transition from biology to joint replacement. The purpose of this study was to investigate the biological response to this procedure. Design: Patients presenting with symptomatic mono- or bicompartmental arthrosis and varus malalignment underwent IA and concurrent medial open wedge high tibial osteotomy (HTO). A subset of patients required hardware removal and consented to second-look arthroscopy without biopsy allowing for assessment of IA components and compartment-specific findings related to implant fixation, cartilage flow, propagation of lesions, and opposing tibial surfaces. Results: In a series of 41 knees (35 patients) treated with combined IA and HTO (mean varus >7°), 26 knees (23 patients, 18 male, 5 female) with a mean age of 52 years (range = 43-67) required HTO plate removal. Concurrent second look arthroscopy was performed at a mean of 14 months (range = 12-19) following the index procedure. On probing, all arthroplasty components showed solid fixation without gap formation. On the medial femoral condyle, 15 mm implants ( n = 14) showed a peripheral cartilage flow of 12% (range = 5% to 25%), 20 mm implants ( n = 12) of 9% (range 5% to 15%), and trochlear implants ( n = 12) of 20% (range 10% to 40%). No progressive deterioration of the index defects or progression of tibial and retropatellar grades were seen. Conclusion: Joint surface reconstruction using IA showed stable fixation with peripheral cartilage coverage ranging from 9% to 20% and no further chondral damage on opposing surfaces. Future clinical effectiveness studies are required to support the positive biological integration.